2020
DOI: 10.31557/apjcc.2020.5.4.251-258
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Outcomes of Breast Cancer in China: Physicians’ Beliefs, Recommendations, and Practices for Breast Cancer Screening

Abstract: Objective: Physicians play a key role in performing and referring patients for cancer screening. A paucity of data exists for breast cancer screening (BCS) recommendations, demographic characteristics, screening practices, and barriers of screening among physicians. The purpose of this project is to examine physicians’ characteristics, practices, and beliefs about BCS recommendations and its barriers. Methods: The study used a descriptive correlational design and 110 surveys were completed. Data was analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…3). Breast cancer is the most common type of malignancy in women and is the second leading cause of cancer-related death (18). Stopping angiogenesis and cell migration in the tumor, exacerbating and inducing cell death by apoptosis, and manipulating cell signaling pathways are promising new strategies in the treatment and control of cancer (19).…”
Section: Resultsmentioning
confidence: 99%
“…3). Breast cancer is the most common type of malignancy in women and is the second leading cause of cancer-related death (18). Stopping angiogenesis and cell migration in the tumor, exacerbating and inducing cell death by apoptosis, and manipulating cell signaling pathways are promising new strategies in the treatment and control of cancer (19).…”
Section: Resultsmentioning
confidence: 99%
“…A culturally and linguistically tailored content was proven to promote accessible health promotion and engagement towards BC screening (Davis and Oakley-Girvan, 2015;H. Lee et al, 2018;Wu et al, 2020). The development of the content has included some facts to encounter some cultural belief.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative approach used to gain insight from the interviews conducted (Francese et al, 2017;Houghton et al, 2019). A previous study reported physicians roles are important in promoting BC screening uptake but some of them encounter problems when patients do not know about BC screening (Wu et al, 2020). Hopefully, the developed mobile application based on the users' requirements involving content and software experts would cater as a health promotion tools targeting breast examination awareness which include information related to BC detection and management.…”
Section: Discussionmentioning
confidence: 99%
“…The advanced cancer presentation among women in China was associated with less knowledge about early detection of cancer. China has launched a variety of programs to promote breast cancer screening, however, the proportion of undergoing breast cancer screening is unsatisfactory (Wang et al, 2013;Wu et al, 2020). A study reported the participation rates (about 21.7%) in breast cancer screening in China was lower than those in Western countries (more than 70%), as well as the goal proposed by the World Health Organization (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A study reported the participation rates (about 21.7%) in breast cancer screening in China was lower than those in Western countries (more than 70%), as well as the goal proposed by the World Health Organization (Wang et al, 2013). Wu et al, (2020) surveyed the physicians in China to explore their breast cancer screening beliefs, recommendations and practice, and found that many physicians might not fully aware of current evidence and screening guidelines, which might result in less breast cancer screening. Thus, training programs about screening guideline should be tailored for physicians to enhance their knowledge, which could improve the screening rates among Chinese women.…”
Section: Discussionmentioning
confidence: 99%